Metode Pengajaran Berbasis Karakter Untuk Anak Usia Dini (Telaah Pemikiran Ratna Megawangi) - Ratna Dewi; Taufik Abdilllah Syukur; Abusiri Abusiri; Tomi Hendra (Institut Agama Islam Negeri Kerinci, Indonesia, 2023)
Character-based teaching methods have become the focus of early childhood education, where early childhood is a very vulnerable level of Education and a unique special approach to the learning process. This study aims to describe and analyze Character-Based Teaching Methods for Early Childhood: An Examination of Ratna Megawangi Thoughts. This study used a qualitative approach by conducting a literature review. This approach shapes children's character through direct learning and practical experience. Meanwhile, the application of character-based teaching methods requires teachers who have a deep understanding of character values to be developed skills in integrating character learning into the curriculum and daily activities, on the other hand also involving parents and the child's social environment in the educational process; to create an environment that supports the development of children's character. The results of this study indicate that there are several teaching methods in kindergarten that can be a concern for educators in developing children's character, including reading, writing and arithmetic schemes, linked to giving grades and report cards, criticism and information on learning outcomes that tend to be negative, class quiet and one-way learning process, as well as intense in the classroom without ice-breaking for a long time.